Mapping global brain reconfigurations following local targeted manipulations - Giovanni Rabuffo; Houefa-Armelle Lokossou; Zengmin Li; Abolfazl Ziaee-Mehr; Meysam Hashemi; Pascale P. Quilichini; Antoine Ghestem; Ouafae Arab; Monique Esclapez; Parul Verma; Ashish Raj; Alessandro Gozzi; et al. (Proceedings of the National Academy of Sciences, 2025)
Understanding how localized brain interventions influence whole-brain dynamics is essential for deciphering neural function and designing therapeutic strategies. Using longitudinal functional MRI datasets collected from mice, we investigated the effects of focal interventions, such as thalamic lesions and chemogenetic silencing of cortical hubs. We found that these local manipulations disrupted the brain’s ability to sustain network-wide activity, leading to global functional connectivity (FC) reconfigurations. Personalized mouse brain simulations based on experimental data revealed that alterations in local excitability modulate firing rates and frequency content across distributed brain regions, driving these FC changes. Notably, the topography of the affected brain regions depended on the intervention site, serving as distinctive signatures of localized perturbations. These findings suggest that focal interventions produce consistent yet region-specific patterns of global FC reorganization, providing an explanation for the seemingly paradoxical observations of hypo- and hyperconnectivity reported in the literature. This framework offers mechanistic insights into the systemic effects of localized neural modulation and holds potential for refining clinical diagnostics in focal brain disorders and advancing personalized neuromodulation strategies.